THE USE OF PREDICTIONS STRATEGY IN IMPROVING STUDENTS’ READING COMPREHENSION - Rusli Sumirat; Cecep Fahmi Rahmat Padilah; Acep Haryudin (IKIP Siliwangi, 2019)
AbstractMany student judge that an English text is very difficult to understand. Consequently they fail to try comprehending a written text and finally they treat reading as the most avoidable activity. Based on the researcher’s observation, the students’ problem through reading comprehension appears because of some factors. The English subject is not easy for them ; they often complain when face it. This condition supports the researchers to make some appropriate learning material and good strategy to improve students’ reading comprehension. This research is aimed to improving students’ reading comprehension on the seventh grade of students at SMP Darussurur Cimahi through the use of prediction strategy. This research used quantitative research design. The population of the research was 194 students from 6 classes and the sample was 36 students from 1 class. The instrument is reading test which consist of 10 items multiple choice, and 10 items of essay. The collected data were analyzed by used SPSS. The result of the analysis showed that the mean score of pretest was 52.36. the mean score of posttest was 76.42. The result of paired samples test for t-test, the value of sig is 0. It is less than 0.05 as the significant level. Therefore, Ho (null hypothesis) is rejected. It means that predictions strategy has significant impact on students’ reading comperhension. The teacher should consider predictions strategy as the alternative technique for teaching reading.Keywords : reading comprehension,predictions strategy, quasi experimental